BEZPIECZEŃSTWO W MIŁOŚCI BOŻEJ. SAKRAMENT MAŁŻEŃSTWA Z PERSPEKTYWY TEOLOGII CIAŁA KAROLA WOJTYŁY - Gerwing, Manfred (Studia Pastoralne, 2023)
Men and women who have received the Sacrament of Marriage and who shape their lives out of this sacrament feel safe in the Trinitarian space of love and feel called to become holy. In his Wednesday catecheses, John Paul II (1979–1984) portrays marriage as a school of holiness. The theology of the body advances and develops in the connection between eros and ethos. A practical sacramental Christian marriage does not only imitate communion with God but furthermore captures and reflects it.